The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jmv.20413
|View full text |Cite
|
Sign up to set email alerts
|

Oral fluid as a medium for the detection of hepatitis B surface antigen

Abstract: Currently viral antigens and antibodies are detected by traditional serological tests. However, the introduction of oral fluid as an alternative medium would allow other alternatives. The collection of oral fluid is, in comparison with venepuncture, less invasive, less painful, less expensive (i.e., no trained personal required), and safe (prevention of needle stick injuries). Also large numbers of samples can be collected easily for epidemiological purposes. Forty-three HBsAg positive and seventy-three HBsAg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
(19 reference statements)
0
25
0
1
Order By: Relevance
“…The prevalence of HBV infection is higher among dentists than the general population, especially among those who have surgical specialties [2][3][4] . The occupational risk of HBV infection through contaminated blood in piercing/cutting accidents among dentists varied between 6% and 30% 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV infection is higher among dentists than the general population, especially among those who have surgical specialties [2][3][4] . The occupational risk of HBV infection through contaminated blood in piercing/cutting accidents among dentists varied between 6% and 30% 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…As a hospital based population remains a selected population, in 2003, the study population was selected from the general public and a saliva test was used because it is not invasive, not painful, less expensive and does not require trained people to collect the sample. Prior to the prevalence study, tests for detection of hepatitis antibody or antigen in oral fluid were validated [2][3][4]. An additional study objective was to evaluate the feasibility of using saliva tests on samples gathered by regular postal services for prevalence study in order to develop a surveillance tool.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have successfully investigated the use of oral fluid or saliva versus serum for the diagnosis of infectious diseases, including infections with HIV (7), hepatitis A virus (8), dengue virus (9), Helicobacter pylori (10), and malaria (11). In addition, antigens, such as hepatitis B surface antigen (12) and Plasmodium falciparum HRP2 malaria antigen (13), and hormones, such as steroids (14), have been assayed in oral fluid. In the field of toxoplasmosis, some authors have already reported the possibility of detecting anti-T. gondii IgG (15,16), IgM, and IgA (17,18).…”
mentioning
confidence: 99%